The identity of the Chilean Amphibians collected by the United States exploring expedition - Lavilla, Esteban O.; Rabanal, Felipe E.; Langone, José A.; Vásquez, Dayana; Castro-Carrasco, Camila (Zootaxa, 2019)
Between mid-May and early June of 1839, members of the United States Exploring Expedition collected diverse anurans in the environs of Valparaíso, Chile, later described by Girard in 1853. Of this set of species, Metaeus timidus, described there as a new genus and species, attracts attention because is a name that practically disappeared from the herpetological literature. Its identification, along with that of the other Chilean taxa collected by the USEE (Cystignathus nebulosus Girard, 1853, Pleurodema bibroni Tschudi, 1838, Pleurodema elegans Bell, 1843, Bufo lugubrosus Girard, 1853, Bufo thaul Lesson, 1826 and Metaeus timidus Girard, 1853) are the main objectives of this contribution.